Experimental analysis of choice behavior in Japanese eel (Anguilla japonica) - Watanabe, Shigeru (Behavioural processes, 2025)
The choice behavior of Japanese eels was analyzed using a generalized matching law. The eels were trained to select between two pipes in a water pool apparatus. Upon entering a pipe, the subjects received reinforcement in the form of a fixed stay duration, which varied from 10 to 2 min, resulting in different reinforcement magnitudes. The application of the generalized matching law successfully predicted the eels' choices and revealed a tendency toward undermatching. Notably, this experiment introduced three novel elements: 1) a new species under study, 2) a novel form of reinforcement, and 3) a discrete trial training method rather than traditional free operant training. These findings broaden the scope of the applicability of the generalized matching law, illustrating its relevance across different species, reinforcement modalities, and training methodologies, thus suggesting universality in the phenomenon of undermatching. •The choice behavior of Japanese eels was analyzed using the generalized matching law.•The generalized matching law accurately predicted the choice behavior of this newly studied species.•The law was validated for choices involving different reinforcement magnitudes.•The findings were supported in the context of discrete trial training.